Gendered Power : Educated Women of the Meiji Empress' Court - Suzuki, Mamiko C. (Book collections on Project MUSE., 2019)
"Drawing on the increased scholarly interest in women of the Meiji period, the present book considers the significance and influence of elite, educated Meiji women and their role in shaping the national identity of women in modern Japan. Carrying over these considerations both from previous English and Japanese scholarship, this study interrogates the political and cultural forces that positioned women as delegates of the Meiji empress' court or as exemplary Japanese women. It argues that the network of women emerging from the empress' court negotiated the visually, culturally, and educationally circulated feminine ideals and its effects that were carried out as components of a modern Japanese woman's identity"--